An Assessment of Teacher Retention on Job Security in Private Secondary Schools in Ogun State, Nigeria - M.F. Faremi (University of Sofia, 2017)
This study assessed the relationship between teacher retention and job security in private secondary schools in Ogun state, Nigeria. The study assessed ade-quacy in teaching and learning infrastructure, evaluated mode of recruitment of teachers, the factors responsible for high teacher turnover and teachers retention strategies employed in private secondary schools. Descriptive research of the survey design was employed in this study. Data were collected using questionnaire. Multistage sampling technique was used for data collection among 200 teachers including the school principals. Data collected were analyzed with a mixture of descriptive and inferential statistics. Percentages, mean and frequency counts were used to answer the research questions raised while Pearson Moment Correlation Coefficient and t-test analysis were used to test the formulated hypotheses at 0.05 level of significance. The findings from this study revealed that teaching and learning infrastructure were inadequate in most of the schools. It was observed that books, classroom and teachers were very adequate in some of the schools. However, few of the schools had internet facility for knowledge transfer and student exposure to the worldwide web. The study also showed that the proprietors were primarily responsible for staff recruitment although there were instances where formal advertisement for recruitment was made. The study further revealed a significant relationship between teacher retention strategies and job security in private secondary schools in Osun state. The study also showed a significant relationship between teacher turnover and job security in the schools. In addition, the findings showed a significant relationship between teacher turnover and job security in private secondary schools in Osun state. Lastly, the study revealed a significant difference in the mean rate and female teachers' turnover in the selected private secondary schools. Based on the findings, it was therefore recommended that teacher retention strategies should include prompt payment of salary, workers welfare packages, good working conditions, teacher mentoring programme, teacher preparation and the provision of basic amenities for effective academic calendar in the secondary schools to ensure job security in private secondary schools.